The Impact of Using Quizizz as a Learning Media on Learning Interest of Computer Education Students - Mesterjon, Mesterjon; Selviani , Diah; Prima Bendrianti , Rita; Rulismi , Dwi; Dali , Zulkarnain (Universitas Islam Indonesia, 2024)
In this case, this research aims to determine the effect of using Quizizz as a learning media on the learning interest of Computer Education Students in the Linear Algebra course. The research method uses quantitative experiments. The research design used One Group Pretest-Posttest Design. The subjects of this research were 38 consisting of 4th Semester Students of the Department of Computer Education, Dehasen University, Bengkulu. The instrument used 20 items questionnaire, the data analysis techniques used normality test, homogeneity test and hypothesis test. The results of the pretest and posttest questionnaires were 40% and 85% indicating an increase in student learning interest. The results of research using paired sample testing show that the asym sig. (2-laid) of 0.000 < 0.05 where t-count is greater than t-table 24.220 > 2.037 so that H_O is rejected and H_a is accepted. It can be concluded that the use of Quizizz as a learning media (X) has a significant effect on the learning interest of computer education students at Dehasen University, Bengkulu.